2017
DOI: 10.1515/jpem-2016-0402
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity and health related quality of life in Iranian children and adolescents: the Weight Disorders Survey of the CASPIAN-IV study

Abstract: The findings or this study support the importance of personal perception and cultural norm roles in HRQOL. Given the association between weight disorders and psychosocial health, it is suggested that social and cultural factors have a more crucial role in the HRQOL of children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 28 publications
9
27
2
Order By: Relevance
“…[27] It appears that total mean PedsQL ™ score is comparative in different areas of Iran using the same score scale. The finding by Hovsepian et al (2017) [26] In this study there was a harmony between children selfreport and parent proxy-report of HRQOL which is in agreement with the results of study by Amiri et al (2012) high parental support in Iranian families can explain the harmony between children self-report and parent proxy-report of HRQOL. [25] this finding is not consistent with results of studies in most of the other translated versions.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…[27] It appears that total mean PedsQL ™ score is comparative in different areas of Iran using the same score scale. The finding by Hovsepian et al (2017) [26] In this study there was a harmony between children selfreport and parent proxy-report of HRQOL which is in agreement with the results of study by Amiri et al (2012) high parental support in Iranian families can explain the harmony between children self-report and parent proxy-report of HRQOL. [25] this finding is not consistent with results of studies in most of the other translated versions.…”
Section: Discussionsupporting
confidence: 91%
“…Although in Hovsepian S et al study, emotional and school functioning domains had a negative association with obesity. [26] The lack of differences in emotional subscale scores across weight categories is consistent with khodaverdi et al [20] this can revealed that obese children despite physical and social difficulties, keep up their emotional health and endeavors for understanding the nature and determinants of constancy to create preventive interventions to advance HRQOL of them will be useful. [41] It appears that different sample size of studies and also cultures of different societies may cause this variety of outcomes in several studies.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations